Influenza Prevalence and Risk Factors: A Population-Based Cross-Sectional Study - Balakrishnan, Kiran Ganesh; Abd Manaf, Mohd Rizal; Hassan, Mohd Rohaizat; Musa, Mohd Kamarul Imran; Mohamad Jamil, Azizul Rahman; Abdul Rahim, Norhaslira; Satariah Ali, Umi Kalsom; Jamal, Rahman (Makara Journal of Health Research, 2023)
Background: Influenza infection can lead to mortality and morbidity. In densely populated Kuala Lumpur, Malaysia, the transmission of influenza-like illness (ILI) is high. This study assessed the prevalence and epidemiology of influenza in the target population. Methods: A cross-sectional convenience sample study was conducted in government clinics of Cheras, Malaysia, from November 1, 2022, to February 28, 2023. Consent was sought from patients older than 18 years with symptoms of ILI (fever, cough, and onset within 10 days). A nasopharyngeal swab preceded an influenza rapid test. Logistic regression was used in SPSS 22.0 to evaluate the data. Results: Among 438 patients, 55 (12.6%) tested positive for influenza type B, 9 (2%) tested positive for type A, and 374 (85.4%) were negative. Patients in the group that was 10 years older than the younger group had 1.47 times the odds of having influenza. The odds of positive influenza rose 1.133 times per unit of body mass index (BMI). Patients with chronic lung illness were 6.7 times (95% confidence interval, 2.742–16.287) more likely to test positive for influenza. Sex and smoking history did not affect the rate of influenza infection (p > 0.05). Conclusions: An association was found between age, BMI, and chronic lung disease with influenza infection but not with sex or smoking.